JOB CREATION LAW: WHAT'S NEXT CHANGE IN INDONESIAN BUSINESS COMPETITION LAW? - Maarif, Syamsul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
The Law Number 11 of 2020 concerning Job Creation amended 79 laws, including Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Far from being comprehensive, the Job Creation Law amended the system of law enforcement regarding business competition that had been in place for over twenty years. With a normative method, this research aims to discuss the legal implications of the effectuation of the Job Creation Law regarding the enforcement of the law concerning business competition. This research reveals that Law 11/2020 could lead to a better legal certainty and adequacy of law enforcement concerning business competition in Indonesia in the time to come.Â